Epigallocatechin-3-Gallate and PEDF 335 Peptide, 67LR Activators, Attenuate Vasogenic Edema, and Astroglial Degeneration Following Status Epilepticus - Ji-Eun Kim; Hana Park; Min-Jeong Jeong; Tae-Cheon Kang (MDPI AG, 2020)
Non-integrin 67-kDa laminin receptor (67LR) is involved in cell adherence to the basement membrane, and it regulates the interactions between laminin and other receptors. The dysfunction of 67LR leads to serum extravasation via blood-brain barrier (BBB) disruption. Polyphenol (-)-epigallocatechin-3-O-gallate (EGCG) and pigment epithelium-derived factor (PEDF) bind to 67LR and inhibit neovascularization. Therefore, in the present study, we investigated the effects of EGCG and NU335, a PEDF-derive peptide, on BBB integrity and their possible underlying mechanisms against vasogenic edema formation induced by status epilepticus (SE, a prolonged seizure activity). Following SE, both EGCG and NU335 attenuated serum extravasation and astroglial degeneration in the rat piriform cortex (PC). Both EGCG and NU335 reversely regulated phosphatidylinositol 3 kinase (PI3K)/AKT-eNOS (endothelial nitric oxide synthase) mediated BBB permeability and aquaporin 4 (AQP4) expression in endothelial cells and astrocytes through the p38 mitogen-activated protein kinase (p38 MAPK) and extracellular signal-regulated kinase 1/2 (ERK1/2) signaling pathways, respectively. Furthermore, EGCG and NU335 decreased p47Phox (a nicotinamide adenine dinucleotide phosphate oxidase subunit) expression in astrocytes under physiological and post-SE conditions. Therefore, we suggest that EGCG and PEDF derivatives may activate 67LR and its downstream effectors, and they may be considerable anti-vasogenic edema agents.